The regulatory pathways of distinct flowering characteristics in Chinese jujube. (1st August 2020) - Meng, Xianwei; Li, Ying; Yuan, Ye; Zhang, Yao; Li, Hongtai; Zhao, Jin; Liu, Mengjun
Abstract: Flowering is the most important event in higher plants. Compared to most fruit tree species, Chinese jujube ( Ziziphus jujuba Mill.), the most important member of the large, diverse Rhamnaceae family and a leading dry fruit-producing species, has unique characteristics that include a short juvenile phase and extremely fast flower bud differentiation. However, the distinct mechanism of flowering regulation in Chinese jujube is still unclear. The morphological and cytological development period of jujube flowering was first investigated, and the crucial developmental stages were defined. Flower bud differentiation in Chinese jujube took only approximately 11–13 days, which is a distinct characteristic of perennial fruit trees. Afterward, 44 genes related to six flowering pathways were identified in the jujube genome and were found to be randomly distributed among 11 of the 12 chromosomes. Tissue-specific and spatiotemporal expression patterns showed that all these genes were expressed in the flowers. Overall, photoperiod-related genes were highly expressed during flower bud differentiation. These genes were also positively responsive to photoperiod regulation and phase change processes, indicating that photoperiod- related genes play crucial roles in jujube flower bud differentiation. Under protected cultivation, ZjPIF4, a temperature-related gene, was expressed in the early stages of flowering and responded to increasing temperatures. Moreover, STRING analysis and yeast two-hybrid screening indicated that photoperiod-related (ZjCO) and temperature-related (ZjPIF4) proteins could interact with ZjFT, the key protein involved in the determination of flowering time, indicating crosstalk between photoperiod-related pathways and ambient temperature-related pathways in jujube. This study is the first report to comprehensively analyze the flowering pathways in Chinese jujube and revealed that photoperiod-related and ambient temperature-related pathways are the main mechanisms regulating the distinct flowering process and that members of the ZjPHY family (ZjPIF4, ZjFT, and ZjCO5) are the key factors involved in the regulatory network. These results will increase our understanding of the molecular and genetic mechanisms of flowering in Chinese jujube and provide meaningful clues for the flowering regulation of other fruit tree species.